HIF1α deficiency reduces inflammation in a mouse model of proximal colon cancer - Dessislava N. Mladenova; Jane E. Dahlstrom; Phuong N. Tran; Fahad Benthani; Elaine G. Bean; Irvin Ng; Laurent Pangon; Nicola Currey; Maija R. J. Kohonen-Corish (The Company of Biologists, 2015)
Hypoxia-inducible factor 1α (HIF1α) is a transcription factor that regulates the adaptation of cells to hypoxic microenvironments, for example inside solid tumours. Stabilisation of HIF1α can also occur in normoxic conditions in inflamed tissue or as a result of inactivating mutations in negative regulators of HIF1α. Aberrant overexpression of HIF1α in many different cancers has led to intensive efforts to develop HIF1α-targeted therapies. However, the role of HIF1α is still poorly understood in chronic inflammation that predisposes the colon to carcinogenesis. We have previously reported that the transcription of HIF1α is upregulated and that the protein is stabilised in inflammatory lesions that are caused by the non-steroidal anti-inflammatory drug (NSAID) sulindac in the mouse proximal colon. Here, we exploited this side effect of long-term sulindac administration to analyse the role of HIF1α in colon inflammation using mice with a Villin-Cre-induced deletion of Hif1α exon 2 in the intestinal epithelium (Hif1αΔIEC). We also analysed the effect of sulindac sulfide on the aryl hydrocarbon receptor (AHR) pathway in vitro in colon cancer cells. Most sulindac-treated mice developed visible lesions, resembling the appearance of flat adenomas in the human colon, surrounded by macroscopically normal mucosa. Hif1αΔIEC mice still developed lesions but they were smaller than in the Hif1α-floxed siblings (Hif1αF/F). Microscopically, Hif1αΔIEC mice had significantly less severe colon inflammation than Hif1αF/F mice. Molecular analysis showed reduced MIF expression and increased E-cadherin mRNA expression in the colon of sulindac-treated Hif1αΔIEC mice. However, immunohistochemistry analysis revealed a defect of E-cadherin protein expression in sulindac-treated Hif1αΔIEC mice. Sulindac sulfide treatment in vitro upregulated Hif1α, c-JUN and IL8 expression through the AHR pathway. Taken together, HIF1α expression augments inflammation in the proximal colon of sulindac-treated mice, and AHR activation by sulindac might lead to the reduction of E-cadherin protein levels through the mitogen-activated protein kinase (MAPK) pathway.